How art places climate change at the heart of technological innovation - Jeanne Bloch; Céline Verchère (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
How can we place climate change issues at the heart of technological innovation? From our point of view, artistic practice is a powerful tool to infuse sustainability dimensions into technological developments. By using a sensitive approach based on a dialogue with his/her inner self, the artist questions the nature and meaning of technological developments and therefore appeals to users' deep motivations. We explore first how the artist inner self engagement in the creation process relates to climate change mitigation. Then, through a qualitative survey-type experimentation derived from Jeanne Bloch's art-tech installation, we expose how the confrontation with a panel of users helps to understand the characteristics of the dialogue an artist engages in with an "immersed" audience, particularly on the issue of climate change.
Keywords: 650; art-thinking; choreography; climate change; dance; food culture; innovation; light design; light pollution; phenomenology; sustainability; visual art